UPAYA MENINGKATKAN HASIL BELAJAR SISWA SMA MELALUI MEDIA PETA KONSEP PADA MATA PELAJARAN BAHASA INDONESIA - Nursari Rindu Simanullang (Universitas Nias Raya, 2022)
The aim of the study was to determine the increase in student learning outcomes in the Indonesian Language Education subject with the subject matter of Debate in class X-Anggrek SMA Negeri 1 Telukdalam using the media concept map for the 2021/2022 Academic Year. The implementation of classroom action research was carried out for two cycles. The results showed that in the first cycle the students' cognitive learning outcomes only reached an average of 61.71 while in the second cycle the students' cognitive learning outcomes experienced an increase with an average learning result reaching 77.75 belonging to the good category. Thus the application of learning media in the form of concept maps can improve students' cognitive learning outcomes. Suggestions put forward by researchers, namely: in learning Indonesian Language Education use concept map media on the subject of debate so that it can improve students' cognitive learning outcomes, should in improving the quality of learning Indonesian Language Education use concept map media, and should use concept map media in teacher learning must prepare the material that will be given properly.